⬇ Hey, the answer is down below! :) ⬇
For y: x = -3
For y it stays the same.
For x: y = 2
For x it stays the same too.
For 1.):
Explanation:
For y there is no step-by-step explanation unfortunately.
For x there isn't a step-by-step explanation too unfortunately.
⬇ For 1.) there is a step-by-step explanation! ⬇
For step 1 we should flip the equations.
6x + 8 = y
For step 2 we should add -8 to both sides.
6x + 8 + − 8 = y + −8
= 6x = y − 8
For step 3 we should divide both sides by 6.
= x =
In result we should have
as the answer!